Advances in Swarm Intelligence Third International Conference, ICSI 2012, Shenzhen, China, June 17-20, 2012, Proceedings, Part II - Tan, Ying; Shi, Yuhui; Ji, Zhen (Theoretical Computer Science and General Issues, 2012)
This book and its companion volume, LNCS vols. 7331 and 7332, constitute the Proceedings of the Third International conference on Swarm Intelligence, ICSI 2012, held in Shenzhen, China in June 2012. The 145 full papers presented were carefully reviewed and selected from 247 submissions. The papers are organized in 27 cohesive sections covering all major topics of swarm intelligence research and developments.